AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL THE HIJAU KEMASAN MEREK X TERHADAP DPPH (2,2 diphenyl-1-picrylhydrazyl) - Alfin Surya (LPPM Universitas Abdurrab, 2019)
This study aims to to determine antioxidant activity in extract methanol of a sample of green tea packaging the brand X to (2,2 diphenyl-1-picrylhydrazyl). A design study used is descriptive qualitative and quantitative antioxidant levels are counting on green tea packing brand X sold in supermarket city Pekanbaru. Antioxidant activity by test 2,2 diphenyl-1-picrylhydrazyl produce inhibitory concentration of 50 extract sample methanol green tea packing x have rata-rata antioxidant activity of 8,7321 ppm .Based on the results of inhibitory concentration of 50 the green tea having a good antioxidant activity.